Free convection boundary layer flow over a horizontal circular cylinder with newtonian heating - Mohd Zuki Salleh,; Roslinda Nazar, (Universiti Kebangsaan Malaysia, 2010)
The numerical solution of steady free convection boundary layer flow over a horizontal circular cylinder, generated by Newtonian heating in which the heat transfer from the surface is proportional to the local surface temperature, is considered. The transformed boundary layer equations are solved numerically using an implicit finite-difference numerical scheme known as the Keller-box method. Numerical solutions are obtained for the skin friction coefficient, local heat transfer coefficient, wall temperature as well as the velocity and temperature profiles. The features of the flow and heat transfer characteristics for large range of values of the Prandtl number are analyzed and discussed.